War: Essays in Political Philosophy by Larry May, ed. (New York: Cambridge University Press, 2008. 325 pages.) (American Journal of Islam and Society, 2010)
There is a long-standing set of criteria thoughtful leaders have used to helpdetermine when engaging in war is the right thing to do. The criteria havealso been long debated, and Larry May’s collection of fifteen original essaysmakes an excellent contribution to the discourse. Historical background isprovided by Gregory Reichberg’s “Jus ad Bellum” and Nicholas Rengger’s“The Jus in Bello in Historical and Philosophical Perspective,” both ofwhich are astutely concise descriptions of just war philosophical developmentfrom the western perspective. Most just war literature readily availableto western analysts has produced by western thinkers, and international legalstandards on war have been promulgated primarily through western interactions.But the rich Islamic tradition of just war jurisprudence and philosophy could have been included. The ninth-century scholar al-Shaybani, forinstance, wrote about the rules of war and has been called “the Hugo Grotiusof Islam.”Al-Farabi, the father of Islamic political philosophy, directly addressesthe justice of war (although significantly the best he will say of any war isthat it is not unjust), and many of his tenth-century principles are consistentwith western thinking; the lack of discrimination between military targetsand civilians is unjust in both traditions, for example. In his SelectedAphorisms, al-Farabi identifies innocents as illegitimate targets and evenhints that forcibly drafted soldiers might be considered “innocents” when thewar’s cause is unjust, thereby intertwining the ad bellum principle of justcause with the in bello principle of discrimination (Political Writings:“Selected Aphorisms” and Other Texts, trans. Charles Butterworth [CornellUniversity Press: 2002]). Thomas Hurka shares al-Farabi’s idea of interdependence.His superb essay, “Proportionality and Necessity,” poses questionssuch as: “How many enemy soldiers can be sacrificed to save one ofour own soldiers’ lives?” According to him, the right number differs accordingto the necessity and who is doing the calculating; in other words, jus adbellum and jus in bello influence each other ...